Asian Tea / Roy Frederick Eden ... [et al.] - Eden, Roy Frederick; Toluod, Fionalin Olivia; Raduan, Dayang Asiyah; Yumin, Lidwina (2013)
Asian tea seeks to provide bottled tea that tastes like tea a world of flavor freshly brewed and barely sweetened. We seek to provide better tasting, healthier teas the way nature and their cultures of origin intended them to be. We strive for relationships with our customers, employees, suppliers and stakeholder where are as healthy and honest as the tea we brew.